INTERACTIVE TECHNOLOGIES AND MUSIC MAKING transmutable music. - Redhead, Tracy ([S.l.] : FOCAL, 2024)
Challenging current music making approaches which have traditionally relied on the repetition of fixed forms when played, this book provides a new framework for musicians, composers, and producers wanting to explore working with music that can be represented by data and transformed by interactive technologies. Beginning with an exploration into how current interactive technologies, including VR and AR, are affecting music, the book goes on to create an accessible compositional model which articulates the emerging field of transmutable music.' It then shows how to compose and produce transmutable music for platforms like video games, apps and interactive works, employing tutorials which use a range of inputs from sensors, data, and compositional approaches. The book also offers technical exercises on how to transform data into usable forms (including machine learning techniques) for mapping musical parameters, and discussion points to support learning. This book is a valuable resource for industry professionals wanting to gain an insight into cutting edge new practice, as well as for assisting musicians, composers, and producers with professional development. It is also suitable for students and researchers in the fields of music/audio composition and music/audio production, computer game design, and interactive media.
Keywords: Electronic music; TECHNOLOGY / Acoustics & Sound